Zastosowanie sieci falkowo-neuronowej do predykcji ekonomicznych szeregów czasowych - Hadaś, Monika (Using Wavelet - Neural Network to Predictive Economic Time Series, 2006)
In this article a deterministic predictive technique is introduced which, is based on the embedding theorem by Takens and the recently developed wavelet networks. Asa result, the predicted values economic time series correspond quite well with the actual values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 69-80